2022
DOI: 10.1007/s12223-022-00973-6
|View full text |Cite
|
Sign up to set email alerts
|

Disease-associated dysbiosis and potential therapeutic role of Akkermansia muciniphila, a mucus degrading bacteria of gut microbiome

Abstract: The unique functionality of Akkermansia muciniphila in gut microbiota indicates it to be an indispensable microbe for human welfare. The importance of A. muciniphila lies in its potential to convert mucin into beneficial by-products, regulate intestinal homeostasis and maintain gut barrier integrity. It is also known to competitively inhibit other mucin-degrading bacteria and improve metabolic functions and immunity responses in the host. It finds a pivotal perspective in various diseases and their treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 130 publications
(120 reference statements)
1
13
0
Order By: Relevance
“…Eubiosis defines the balanced qualitative and quantitative condition of the intestinal microflora, and is essential to preserving the host’s health. On the contrary, its qualitative/quantitative perturbation, namely, dysbiosis, is associated with the development of various diseases such as NAFLD, NASH until HCC [ 59 , 60 ], diabetes type 2, cardiovascular disorders, and, undoubtedly, obesity [ 61 , 62 ] ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eubiosis defines the balanced qualitative and quantitative condition of the intestinal microflora, and is essential to preserving the host’s health. On the contrary, its qualitative/quantitative perturbation, namely, dysbiosis, is associated with the development of various diseases such as NAFLD, NASH until HCC [ 59 , 60 ], diabetes type 2, cardiovascular disorders, and, undoubtedly, obesity [ 61 , 62 ] ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we showed that A. muciniphila, F. prausnitzii, and B. vulgatus, which are well-known as microbiota of the gastrointestinal tract, and their abundance were higher for I compared to II and III groups respectively in our study. These bacteria species deserve special attention being responsible for mucin degradation [30][31][32][33], which might lead to direct contact of mucosa and induce inflammation. The respiratory and gastrointestinal tracts share a common mucosal immune system known as the gut-lung axis [34].…”
Section: Discussionmentioning
confidence: 99%
“…It colonizes the gut very early, during the first year of life, via human milk [ 73 ]. Thereby, it is highly abundant in the gut of infants and healthy adults, accounting for 0.5–5% of the human gut microbiota [ 72 , 73 , 74 ]. Its beneficial effects are mainly attributed to its ability to degrade mucin: a major component of mucus in the gut [ 74 ].…”
Section: Preventive and Therapeutic Potential Of Ngps In Obesity And ...mentioning
confidence: 99%